AWS Certified Cloud Practitioner : LiveLessons (LiveLessons (Indianapolis, Ind.), 2018)
"AWS Certified Cloud Practitioner Complete Video Course is a video product designed to help viewers understand Amazon Web Services at a high level, introduce cloud computing concepts, and key AWS services, and prepare them for the exam according to the certification exam guide published by Amazon Web Services."--Resource description page